IMPLEMENTATION OF COMIC LEARNING MEDIA TO IMPROVE UNDERSTANDING OF HISTORY AND CULTURE - Ridwan, Ridwan; Sari, Rima Meilita; Islami, Zukya Rona (JURNAL EDUSCIENCE, 2025)
Purpose – This study aims to analyze the improvement of students' understanding of history and culture through the implementation of the Putri Nurul 'Akla historical comic learning media.Methodology – The approach employed is quantitative, utilizing data collection techniques that include observation, questionnaires, and tests. Data validity was assessed using SPSS for Windows, version 21, with 40 respondents. The analysis was carried out by comparing the t-count and t-table values.Findings – The results showed that t-count (8.662) > t-table (1.729), indicating a significant influence of implementing comic media on improving the understanding of history and culture among grade V students of Cot Keh Peureulak Elementary School, East Aceh.Contribution – This research makes a theoretical contribution by enriching the literature on the use of culture-based learning media, specifically historical comics, as an effective tool for enhancing students' cognitive understanding. To enhance pedagogical practices and foster students' appreciation of cultural heritage, this research provides teachers with creative teaching resources that incorporate local history and culture into the curriculum.